Epithelial stem cells from human small bronchi offer a potential for therapy of idiopathic pulmonary fibrosisResearch in context - Zeyu Liu; Qi Zheng; Zhoubin Li; Moli Huang; Cheng Zhong; Ruize Yu; Rong Jiang; Haotian Dai; Jingyuan Zhang; Xiaohua Gu; Yongle Xu; Chunwei Li; et al. (EBioMedicine)
Summary: Background: Idiopathic pulmonary fibrosis (IPF) is a fibrosing interstitial pneumonia with restrictive ventilation. Recently, the structural and functional defects of small airways have received attention in the early pathogenesis of IPF. This study aimed to elucidate the characteristics of small airway epithelial dysfunction in patients with IPF and explore novel therapeutic interventions to impede IPF progression by targeting the dysfunctional small airways. Methods: Airway trees spanning the proximal–distal axis were harvested from control lungs and explanted lungs with end-stage IPF undergoing transplant. Qualified basal cells (BCs, p63/Krt5/ITGA6/NGFR) were expanded, and their cellular functions, feasibility, safety and efficacy for transplantation therapy in IPF were validated with experiments in vitro and mouse model. Single-cell RNA-sequencing was employed to elucidate the underlying mechanisms governing the BCs based therapy. Based upon these evidences, three patients with advanced IPF and small airway dysfunction received autologous-BCs transplantation. Post-transplantation assessments included lung function, exercise capacity and high resolution computed tomography (HRCT) scans were analyzed to quantify the clinical benefits conferred by the BCs transplantation. Findings: An overall landscape of senescent phenotype in airway epithelial cells and airway stem/progenitor cells along the proximal–distal axis of the airway tree in IPF were outlined. In contrast to the cells situated in distal airways, BCs located in small bronchi in IPF displayed a non-senescent phenotype, with comparable proliferative, differentiative capabilities, and similar transcriptomic profiles to normal controls. In a mouse model of pulmonary fibrosis, BCs exhibited promising protective efficacy and safety for transplantation therapy. Autologous BCs transplantation in three advanced IPF patients with small airway dysfunction yielded significant clinical improvements in pulmonary function, particularly evidence in lung volume and small airway function. Interpretation: Epithelia of small bronchi in IPF contain functional and expandable basal stem cells, which exert therapeutic benefits via bronchoscopic implantation. Our findings offer a potential for IPF treatment by targeting small airways. Funding: National Natural Science Foundation of China (82430001, 81930001, and 81900059), Shanghai Shenkang Hospital Development Center (SHDC2020CR3063B), Department of Science and Technology of Shandong Province (2024HWYQ-058).